Drought stress induced the flavonoid content in Moringa (Moringa oleifera Lam.) leaves - Ridwan,; Hamim,; Suharsono,; Nuril Hidayati, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Flavonoid is one of the most widely available bioactive compounds presence in the Moringa (Moringa oleifera Lam.) leaves. Osmotic stress is known to induce flavonoid production, however, the water level varies among plant species. This study aimed to examined the effects of water stress levels on the flavonoid content of Moringa leaves. The plants were treated withholding watering at three intervals (I): i.e.,: 1 (as control), 3 and 7 days based on the evaporated water during the treatments. The drought treatments were given within 4 different periods (D) before the plants were harvested, i.e.,: 8, 16, 24 and 32 days, and measured for the growth and biomass, proline (Pro) and chlorophyll (Chl) content, leaf water potential (WP), leaf relative water content (RWC), quercetin (Q) and kaempferol (K) content, and water use efficiency of flavonoid (WUEf). The results showed that the drought treatments induced different water statuses in the plants by decreases the leaf relative water content (RWC) and leaf water potential (WP) and increases of proline content significantly (up to 3 fold). Growth and biomass production decreased with the increase of water stress, whereas flavonoid content increased when the drought was mild and decreased again under severe drought. The highest content of flavonoids (1314.53 mg/kg leave biomass for Q and 2984.15 mg/kg leave biomass for K) and WUEf were shown when the plants were treated with 3 days drought for 16 days periods before the plants were harvested (I2D2) with no significant reduction in leaf biomass. This result suggests that the treatment of I2D2 is the best for bioactive production in Moringa.